From the Road Movie to Wilderness Travel: The Quest for Adventure on the Road and the Myth of the Heroic Traveller - Pascale Argod (Via@)
The conceptions of ‘wild’, as addressed in fictional travel diary films, question our relationship with space and the form of travel that gives rise to self-transcendence through a confrontation with the environment. The lived experience of the journey of discovery (adventure, exploration, expedition) defines the travel diary genre, which has become an off-the-beaten-track tourism medium. The reference points for two American travel diary films Into the Wild (2007), written and directed by Sean Penn, and Wild (2014, directed by Jean-Marc Vallée, are Jack Kerouac’s On the Road and the American pioneer front. These films mark a generation of travel diarists in search of the dream and anti-travel. The return to the wild, as a cultural confrontation, formative journey and self-transcendence, is said to shape the travel diary genre, which takes the form of either a piece of self writing or an autobiographical film (sometimes called a biopic) on the experience of travelling. We thus extend the road movie genre to robinsonades and films on the experience of a natural environment. The aesthetics of the image, panoramic landscape and grandeur of nature are thought to be a legacy of the notions of ‘picturesqueness’ and the ‘pioneer front’, while the renewed myths of both the wandering hero (Benoliel, 2011) and the quest for a new world seem to have developed from the literary references of On the Road and the Beat Generation’s ‘Beat ethos’.